Developing Arabic Language Learning Media Based on Lectora Inspire 17 Applications for Junior High School - Jauhar Ali; Ayu Tiffani Maulida; Muhammad Ulil Fahmi; R. Umi Baroroh (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The prevailing methods of Arabic language instruction predominantly rely on didactic approaches involving lectures and memorization, contributing to a waning interest and motivation among students. This pedagogical challenge is exacerbated by the disruption caused by the COVID-19 pandemic, which has significantly impeded traditional learning activities in schools. In response to these impediments, the development of Arabic language learning media utilizing the Lectora Inspire 17 application emerges as a viable solution, fostering an environment conducive to engaging and self-directed learning. This research endeavors to construct an android-based Arabic learning medium employing the Lectora Inspire 17 application. The focus lies on assessing the efficacy and viability of the developed learning media at MTs Hidayatul Athfal Banyurip Alit Pekalongan. Employing the ADDIE development model method (Analysis, Design, Development, Implementation, and Evaluation), this study conducts a comprehensive examination of the media's feasibility. The evaluation conducted by media experts yielded a favorable percentage of 82%, placing the developed media in the feasible category. Moreover, assessments by subject matter experts resulted in an impressive percentage of 90%, categorizing the material as highly feasible. Notably, students' responses to the learning media demonstrated a substantial approval rate of 90% in the highly feasible category. Consequently, it is evident that the Arabic language learning media based on the Lectora Inspire 17 android application is well-suited to serve as an effective educational tool.